Pengaruh Digital Marketing Dan Brand Image Terhadap Loyalitas Konsumen Aplikasi Shopee Di Kota Makassar Dengan Mediasi Repurchase Intention - Zulfiana Ana; Syamsu Nujum; Abbas Selong (Economics and Digital Business Review, 2024)
This study aims to analyze digital marketing affecting consumer loyalty of the Shopee application in Makassar City; to analyze the brand image affecting consumer loyalty of the Shopee application in Makassar City; to analyze digital marketing affecting the repurchase intention of the Shopee application in Makassar City; to analyze the brand image effect on the repurchase intention of the Shopee application in Makassar City; to analyze repurchase intention affecting consumer loyalty of the Shopee application in Makassar City; to analyze repurchase intention able to mediate the influence of digital marketing on consumer loyalty of the Shopee application in Makassar City; to analyze repurchase intention is able to mediate the influence of brand image on consumer loyalty of the Shopee application in Makassar City. This research approach uses a scientific approach. In this study, the target population is all consumers who have made purchases on the Shopee application in Makassar City. By using purposive sampling, the total sample was 105 respondents who used the Shopee application in Makassar City. The results of this study show that Digital Marketing has a positive and significant effect on consumer loyalty; Brand image has a positive and significant effect on consumer loyalty; Digital marketing has a positive and significant effect on repurchase intention; Brand image has a positive and significant effect on repurchase intention; repurchase intention has a positive and significant effect on consumer loyalty; repurchase intention is able to mediate the influence of digital marketing on consumer loyalty; Repurchase intention is able to mediate the influence of brand image on consumer loyalty.